Off The Margin: Portrayal of Slavery in Guru Prasad Mainali’s Short Fictions (Pragya Darshan प्रज्ञा दर्शन, 2024)
Guru Prasad Mainali’s literary accomplishment Naso [The Ward] portrays the issues of slavery in the late 1920s in Nepal. The collection of eleven stories has two specific stories that deal with the issue of the former slaves: “Papko parinam” [The results of misdeeds] (1927) and “Naso” [The ward] (1935) depict the life of the people who once lived the life as slaves. Mainali draws his characters from Nepali society after Chandra Shumsher abolished slavery in Nepal in 1924. Mainali presents them in the most humane form, struggling to settle themselves into an organized society after their emancipation from the bondage of slavery. “Papko parinam” (1927) builds the world around their quest placing the former slaves at the center stage, while “Naso” (1935) pictures former slave Nauli in a functional role to bring Devi Raman’s first wife Subhadra back to her house from Kathmandu. Both stories leave traces of slavery and the issues surrounding the era of fundamental change in the history of Nepal. Mainali sets the events in the background of the change in the 1920s and unfolds his story of Devi Raman and Shubhadra in "Naso" and Kanta Padhya in "Papko Parinam." This paper rereads Mainali’s two fiction in the historical backdrop to get into the world of slavery as depicted in them and conclude that Nepali fiction has dealt with the issue of slavery in the 1920s.